Veterinary medical terminology - Christenson, Dawn E. (W. B. Saunders company, 1997)
Here's a text that provides readers with a solid foundation in veterinary medical terminology. A strong emphasis on clinical application makes the vocabulary easy to learn and remember, and familiarizes readers with basic concepts in anatomy, physiology, and disease. Features chapter goals and objectives, self-tests with answers, numerous illustrations, and much more!